Spore-Derived Isolates from a Single Basidiocarp of Bioluminescent Omphalotus olivascens Reveal Multifaceted Phenotypic and Physiological Variations - Rudy Diaz; David Bermudes (Microorganisms)
The fungal genus Omphalotus is noted for its bioluminescence and the production of biologically active secondary metabolites. We isolated 47 fungal strains of Omphalotus olivascens germinated from spores of a single mushroom. We first noted a high degree of variation in the outward appearances in radial growth and pigmentation among the cultures. Radial growth rates fell into at least five distinct categories, with only slower-growing isolates obtained compared with the parental dikaryon. Scanning UV-vis spectroscopy of liquid-grown cultures showed variation in pigmentation in both the absorption intensity and peak absorption wavelengths, indicating that some isolates vary from the parental strain in both pigment concentration and composition. Bioluminescence intensity was observed to have isolates with both greater and lesser intensities, while the increased emission in response to caffeic acid was inversely proportional to the unstimulated output. Under UV illumination, the media of the parental strain was observed to be brightly fluorescent, which was not due to the pigment, while the isolates also varied from greater to lesser intensity and in their peak emission. At least three separate fluorescent bands were observed by gel electrophoresis from one of the cultures, while only one was observed in others. In a subset of the cultures, fluorescence intensity varied significantly in response to casamino acids. None of this subset produced an antibiotic effective against Staphylococcus aureus, and only the haploids, but not the parental heterokaryon, produced an antibiotic consistent with illudin M effective against Mycobacterium smegmatis. This same subset produced an anticancer agent that was highly potent against MDA-MB-468 breast cancer tumor cells. We interpret these variations in haploids as significant in altering Omphalotus physiology and its production of secondary metabolites, which may in turn alter their ecology and life cycle, and could be further applied to studying fungal physiologies and facilitate linking them to their genetic underpinnings.